Rich Crime, Poor Crime : Inequality and the Rule of Law - Webster, Colin (Criminologist) (Emerald Publishing Limited, 2023)
An important and challenging book comprehensively spanning across the establishment of power systems, Rich Crime, Poor Crime is a vital read for academics, professionals and those interested in the fields of history, sociology, criminology, and politics.